Increased Risk of Recurrent Acute Respiratory Infections in Children with Congenital Heart Disease: A Prospective Cohort Study - Mulyadi Muhammad Djer; Emilda Osmardin; Badriul Hegar; Darmawan Budi Setyanto (The Indonesian Biomedical Journal, 2020)
BACKGROUND: There is a lack of local data about recurrent acute respiratory infections in children with congenital heart disease (CHD). This study aims to investigate the incidence and recurrence of acute respiratory infection (ARI) in left-to-right shunt CHD.METHODS: This prospective cohort study investigated children with left-to-right shunt CHD, aged three months to five years, at Dr. Cipto Mangunkusumo Hospital between September 2012 and April 2013. Age and sex-matched participants without CHD were recruited as reference. The occurrence of ARI was observed for six months. Acyanotic CHD patients from 2015 to 2019 were also evaluated to determine the proportion of ARI among this population.RESULTS: A total of 100 subjects were enrolled in the study, 50 in the CHD group and 50 in the non-CHD group, six of whom were later excluded. The monthly incidence of ARI in the CHD group ranged between 40-60% (p=0.027). Subjects with CHD had a cumulative increased risk of 10% for acquiring ARI (RR=1.1; 95% CI=1.02-1.2, p=0.027). The proportion of subjects with a high recurrence of ARI was also higher in the CHD compared to the non-CHD group (67% vs. 30 %, p<0.001). The mean frequency of and median duration of ARI episodes was also higher in CHD compared to the non-CHD group, 3 vs. 1.5 episodes (p<0.001), and 7 vs. 5 days, respectively.CONCLUSION: Children with CHD are at an increased risk of ARI, with more episodes and longer duration compared to children without CHD.KEYWORDS: non-cyanotic CHD, left-to-right shunt, acute respiratory infections